Hodnocení finanční situace podniku a návrhy na její zlepšení - Muchová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce zhodnocuje finanční situaci podniku Ireks Enzyma, s.r.o. v letech 2016 až 2020. Práce je rozdělena na 3 části, první z nich představuje teoretickou stránku práce, jako je vysvětlení jednotlivých ukazatelů a výpočtů k nim vedoucím. Tyto znalosti jsou poté prakticky využity v další části, která využívá účetních výkazů podniku a ukazatelů z nich postupně vypočítaných. V poslední, třetí, části je provedena analýza vnitřního a vnějšího prostředí podniku pomocí SWOT, PESTEL a Porterovy analýzy. V neposlední řadě následuje ukončení práce souhrnným zhodnocením finanční analýzy podniku Ireks Enyzma, s.r.o. s návrhy možných řešení zjištěných nedostatků.

The bachelor’s thesis is focused on evaluation of selected company’s (Ireks Enzyma, s.r.o.) financial situation during five years - between 2016 and 2020. This thesis is compartmented into three sections: the first one represents theoretical knowledge (such as explanation of the financial analysis indicators) which is then practically used in the next part of the thesis – this (second) part utilises financial statements of the company and indicators calculated from it. In the last, third, part of the bachelor’s thesis, an analysis of both internal and external surroundings of the company is performed - using SWOT, PESTEL and Porter analysis. Last but not least, the thesis is accomplished by a comprehensive financial analysis evaluation of the company Ireks Enzyma, s.r.o., provided with some suggestions of detected deficiencies improvement.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: Finanční analýza; rozvaha; výkaz zisků a ztrát; cash flow; likvidita; rentabilita; ukazatele aktivity; Quick-test; Index bonity; Altmanův model; Z-skóre; IN05; Porterova analýza; PESTEL; SWOT; Financial analysis; banace sheet; profit and loss statement; cash flow; liquidity; profitability; acitivity ratios; Quick-test; bonity index; Altman analysis; Z-score; IN05; Porter analysis; PESTEL; SWOT